«The Easter World» of Nicholas II during the Bell for Witte Tolled - Nelly Mikhailovna Tairova (Управленческое консультирование, 2018)
The Easter world of Nicholas II, the so-called family world of the Russian tsar brought him rest, happiness, love. A special role was played by two types of traditions in days of the Easter holiday: “aristocratic” when the tsar gave to beloveds (mother and the wife) precious eggs of the famous jeweler Karl Faberge and “national” - the tsar as “owner” of all Russia in day the Saint Easter paternally kissed relatives and soldiers, that is on orthodox custom exchange a triple kiss with citizens and gave porcelain eggs from Faberge. The Easter world of Nicholas II is reminiscence of happy moments in life of his family and triumphal events in days of his rule.